Effects of selected fruit development factors on the quality and acceptability of vacuum-fried EVIARC sweet jackfruit (Artocarpus heterophylus Lam.) pulp - Lauzon, Roberta D.; Galvez, Lorina A.; Amestoso, Felix J.; Vinculado, Jennelyn P. (Annals of Tropical Research, 2019)
The study was undertaken to evaluate the effects of fruit development and conditions on the quality and acceptability of fresh and vacuum-fried jackfruit pulp from EVIARC Sweet variety. Four maturity periods, namely, 85, 88, 91 and 94 days after bagging of fruits were considered in the study. Effect of fruit location on tree and pulp location in fruit, as well as size and thickness of pulp were the conditions evaluated. Physicochemical properties like pH, TTA, TSS, thickness and pectin of fresh ripe pulp were evaluated while sensory attributes of vacuum-fried jackfruit pulp were determined. The attributes evaluated by semi-trained panelists were color, aroma, taste, texture, oiliness and general acceptability of vacuum-fried jackfruit pulp. Consumer acceptability was determined by subjecting the product to consumer evaluation employing students, faculty, staff, housewives and guests of the Visayas State University. It was found that fruit maturity significantly affected the quality of vacuum-fried jackfruit pulp. The ideal maturity of jackfruit for vacuum fried pulp production is 88 days after bagging. Fruit location on tree has significant influence on pH, TSS and TA while the pulp location in fruit has significant influence on pH, TSS and thickness. The pulp thickness did not influence the sensory acceptability ratings of all the sensory attributes. The pulp size only influenced the taste acceptability rating of the product. The taste attribute of vacuum-fried jackfruit pulp was significantly affected by the fruit location on tree, location of pulp in fruit, and pulp size. Worth noting is that mean acceptability rating still fell under the moderately acceptable level of the scale and the products were acceptable among consumers.